Light Is the Primary Driver of Early Season Phytoplankton Production Along the Western Antarctic Peninsula. Issue 11 (7th November 2019) - Joy‐Warren, Hannah L.; van Dijken, Gert L.; Alderkamp, Anne‐Carlijn; Leventer, Amy; Lewis, Kate M.; Selz, Virginia; Lowry, Kate E.; van de Poll, Willem; Arrigo, Kevin R.
Abstract: Light and dissolved iron (dFe) availability control net primary production (NPP) in much of the Southern Ocean, but the primary controller during spring in the western Antarctic Peninsula has never been assessed. Underwater light and dFe availability are sensitive to climate‐induced changes in upper ocean circulation, stratification, and sea ice cover, which can affect NPP and phytoplankton community composition, both of which can alter carbon drawdown and food web structure. We estimated in situ NPP, net community production, and heterotrophic respiration and contextualized our field measurements with satellite‐based historical NPP estimates. Average light exposure mainly controlled NPP, while low dFe was associated with greatest NPP, indicating that spring phytoplankton growth is light‐limited and not dFe‐limited. Using experiments that simulated varying mixed layer depths by exposing phytoplankton to a short period of in situ surface light (up to 150× the mean light in the mixed layer, comparable to the difference in light experienced by phytoplankton mixed from 50 m to the surface), we assessed the effect of phytoplankton photoacclimation on NPP and relative success of individual taxa. At moderate light exposure (<30×), phytoplankton experienced little photodamage or changes in NPP, and Phaeocystis antarctica grew more than diatoms. Conversely, phytoplankton exposed to high light (>60×) experienced significant photodamage, declines in NPP, and declines in P. antarctica, with no consistent changes in diatoms. These results support the idea that P. antarctica is better adapted to variable light than diatoms and suggest that deeper mixed layers with variable light will favor P. antarctica . Plain Language Summary: Phytoplankton are single‐celled marine photosynthetic organisms that require sunlight and nutrients to grow, but climate change is rapidly altering their environment. Marine animals depend either directly or indirectly on phytoplankton for food, so changes in phytoplankton impact the entire ecosystem. We studied whether lack of light or nutrients limits spring phytoplankton growth in the ocean near Antarctica. Although by spring there are many hours of sunlight, ice on the surface of the ocean partially blocks sunlight from reaching phytoplankton. Similarly, phytoplankton have access to most nutrients they need for growth but often lack iron. Field measurements showed that phytoplankton growth was limited by light, despite low iron. In experiments, we exposed phytoplankton to short periods of high light, simulating mixing. One type of phytoplankton ( Phaeocystis ) grew more when given extra light, while the other (diatoms) was not affected. Because the two phytoplankton types are eaten by different organisms and have distinct impacts on carbon cycling, these differences are important for the future of the ecosystem. If light intensity changes from low to high quickly—for example, if ice melts earlier in spring due to climate change—the relative proportion of Phaeocystis may increase, altering the food web and carbon cycling. Key Points: Net primary production in the spring is controlled by mean light in the mixed layer Phytoplankton experienced some cellular damage from exposure to 30× higher light Light exposure stimulated P. antarctica growth and minimally affected diatom growth